(untitled) (Bangladesh Journal of Pharmacology, 2015)
Premna serratifolia (Syn: Premna integrifolia) is an important medicinal herb known as Agnimantha in Ayurveda and traditionally used for anticancer activity. The objective of present study was to isolate the cytotoxic phytoconstituents from the n-hexane soluble fraction of P. serratifolia leaf extract. Unsaponifiable portion of n-hexane soluble fraction was subjected to silica based column chromatography. The major constituents present in all the sub-fractions were identified by TLC and phytochemical tests. Two constituents were isolated and they were purified. Sub-fractions with isolates were tested for cytotoxic effect by BSL bioassay. Two isolates were found to be active and which were tested on cancer cell lines MCF-7 and HT-29 for their cytotoxicity. Among two isolates, one compound has shown significant cytotoxicity. From the results we conclude that the plant isolates showed cytotoxicity against selected human cancer cell lines.